Metallomic study on the metabolism of RAPTA-C and cisplatin in cell culture medium and its impact on cell accumulation. Issue 3 (27th February 2018) - Holtkamp, Hannah U.; Movassaghi, Sanam; Morrow, Stuart J.; Kubanik, Mario; Hartinger, Christian G.
Abstract : The different extracellular speciation of cisplatin and the organoruthenium developmental anticancer agent RAPTA-C impacts the accumulation in cancer cells. Abstract : Metal-based anticancer agent development can be improved with advanced metallomics methods that allow for quick and efficient screening of metallodrugs for their metabolites in biological media. Cellular accumulation in in vitro settings is not always correlated with cytotoxicity; and protein binding, particularly with albumin and transferrin, can have an important influence on metallodrug transportation, selectivity, and efficacy. We contrast the time-dependent cellular accumulation of both cisplatin and the pre-clinically investigated RAPTA-C in terms of cell uptake and speciation in culture medium via CE-ICP-MS analysis. Despite RAPTA-C being administered at 40-fold higher dose than cisplatin, owing to its much higher IC50 value, the accumulation over time was only 10-fold higher. An optimised CE-ICP-MS method, through the coating of the capillary to prevent protein–capillary surface interactions, resulted in superior resolution and metal–protein adduct identification. It was then used for extracellular speciation in conjunction with [tris(acetylacetonato)cobalt(iii )] as an internal standard. RAPTA-C was found to be more inert to extracellular reactions than cisplatin which could be used to rationalise the observed cellular uptake patterns. While for cisplatin both transferrin and albumin were identified as the main binding partners, RAPTA-C was found to react nearly exclusively with albumin. Moreover, this behaviour was time-dependent and our results also demonstrate that cancer cells have an influence on metal species distribution in the cell culture medium over time.